Dairy Products Made from Yogurt in Hatay Region - Dilek Say; Mehmet Salih Çayır; Nuray Güzeler (Turkish Journal of Agriculture: Food Science and Technology)
In Hatay region, production of dairy products whose raw material is known as yogurt is important to increase the durability of yogurt. These products are produced in small-scale enterprises and offered for sale in local markets, and in some enterprises are produced industrially. It is also made by the local people for their own consumption. Dairy products made from yogurt in and around Hatay; Concentrated (torba) Yogurt, Salted Yogurt, Duberke, Labne (labna modavara, junkie, labna mıdabale), Çökelek, Antakya Sürk (Antakya Çökelek) which have geographically indicated, Yogurt Cheese and Butter made from yogurt (yayık butter). In this study, production technology, general characteristics and studies related to the subject of dairy products made from yoghurt were given.